Function Characterization of Endogenous Plasmids in Cronobacter sakazakii and Identification of p-Coumaric Acid as Plasmid-Curing Agent - Ji, Xuemeng; Lu, Ping; Hu, Yaozhong; Xue, Juan; Wu, Jing; Zhang, Bowei; Zhang, Yan; Dong, Lu; Lv, Huan; Wang, Shuo (Frontiers in Microbiology, 2021)
Virulence traits and antibiotic resistance are frequently provided by genes located on plasmids. However, experimental verification of the functions of these genes is often lacking due to a lack of related experimental technology. In the present study, an integrated suicide vector was used to efficiently and specifically delete a bacterial endogenous plasmid in Cronobacter sakazakii. The pESA3 plasmid was removed from C. sakazakii BAA-894, and we confirmed that this plasmid contributes to the invasion and virulence of this strain. In addition, the pGW1 plasmid was expunged from C. sakazakii GZcsf-1, and we confirmed that this plasmid confers multidrug resistance. We further screened plasmid-curing agents and found that p-coumaric acid had a remarkable effect on the curing of pESA3 and pGW1 at sub-inhibitory concentrations. Our study investigated the contribution of endogenous plasmids pESA3 and pGW1 by constructing plasmid-cured strains using suicide vectors and suggested that p-coumaric acid can be a safe and effective plasmid-curing agent for C. sakazakii.